Drivers for low-value imaging: a qualitative study of stakeholders' perspectives in Norway - Ingrid Øfsti Brandsæter; Eivind Richter Andersen; Bjørn Morten Hofmann; Elin Kjelle (BMC, 2023)
Abstract Background One kind of overutilization of diagnostic imaging is low-value imaging, i.e., imaging that does not lead to altered clinical pathways or improved health outcomes. Despite having well-documented extension and consequences, low-value imaging is still widespread. The objective of this study was to identify the drivers for the use of low-value imaging in the Norwegian healthcare services. Methods We conducted individual, semi-structured interviews among representatives from the health authorities, general practitioners, specialists working in hospitals, radiologists, radiographers, and managers of imaging departments. Data analysis was carried out in line with framework analysis consisting of five steps: Familiarization, indexing, charting, mapping, and interpretation. Results The analysis included 27 participants and resulted in two themes. The stakeholders identified drivers in the healthcare system and in the interaction between radiologists, referrers, and patients. The identified drivers were categorized in sub-themes, such as organization, communication, competence, expectations, defensive medicine, roles and responsibilities, and referral quality and time constraints. The drivers interact with each other and may strengthen the effect of other drivers. Conclusions Several drivers for low-value imaging in Norway were identified at all levels of the healthcare system. The drivers work simultaneously and synergistically. To free resources for high-value imaging, drivers should be targeted by appropriate measures at several levels to reduce low-value imaging.